Identifying the top research priorities in postmastectomy breast cancer reconstruction: a James Lind Alliance priority setting partnership - Toni Zhong; Katherine Cowan; Geoff Porter; Claire Temple-Oberle; Kelly Metcalfe; Anisha Mahajan; Martin LeBlanc (BMJ Open)
Background Major improvements in breast cancer treatment in the last decade include advancements in postmastectomy breast reconstruction (PMBR). Unfortunately, the studies in PMBR are primarily researcher or industry led with minimal input from patients and caregivers. The aim of this study is to use the James Lind Alliance (JLA) approach to bring together the patients, caregivers and clinicians in a priority setting partnership to identify the most important unanswered research questions in PMBR.Methods The JLA priority setting methodology involved four key stages: gathering research questions on PMBR from patients, caregivers and clinicians; checking these research questions against existing evidence; interim prioritisation and a final consensus meeting to determine the top 10 unanswered research questions using the modified nominal group methodology.Results In stage 1, 3168 research questions were submitted from 713 respondents across Canada, of which 73% of the participants were patients or caregivers. Stage 2 confirmed that there were a total of 48 unique unanswered questions. In stage three, 488 individuals completed the interim prioritisation survey and the top 25 questions were taken to a final consensus meeting. In the final stage, the top 10 unanswered research questions were determined. They cover a breadth of topics including personalised surgical treatment, safety of implants and newer techniques, access to PMBR, breast cancer recurrence and rehabilitation.Interpretation Identification of the top 10 unanswered research questions is an important first step to generating relevant and impactful research that will ultimately improve the PMBR experience for patients with breast cancer.